Dairy development in Ethiopia - Ahmed, Mohamed A. M.; Ehui, Simeon; Yemesrach, Assefa (International Food Policy Research Institute, 2004)
Ethiopia holds large potential for dairy development due to its large livestock population, the favorable climate for improved, high-yielding animal breeds, and the relatively disease-free environment for livestock. Given the considerable potential for smallholder income and employment generation from high-value dairy products, development of the dairy sector in Ethiopia can contribute significantly to poverty alleviation and nutrition in the country. Like other sectors of the economy, the dairy sector in Ethiopia has passed through three phases or turning points, following the economic and political policy in the country. In the most recent phase, characterized by the transition towards market-oriented economy, the dairy sector appears to be moving towards a takeoff stage. Liberalized markets and private sector investment and promotion of smallholder dairy are the main features of this phase. Milk production during the 1990s expanded at an annual rate of 3.0 percent compared to 1.63-1.66 percent during the preceding three decades. Review of the development of dairy sector in Ethiopia indicates that there is a need to focus interventions more coherently. Development interventions should be aimed at addressing both technological gaps and marketing problems. Integration of crossbred cattle to the sector is imperative for dairy development in the country. This can be achieved either through promotion of large private investment to introduce new technology in the sector such as improved genotypes, feed and processing, and promotion of integration of crossbred cattle into the smallholder sector through improving their access to improved cattle breeds, AI service, veterinary service, and credit. Similarly, government should also take the lead in building infrastructure and providing technical service to smallholders. Severe shortages, low quality and seasonal unavailability of feed likewise remain as major constraints to livestock production in Ethiopia. These constraints need to be addressed and technological change be promoted to increase milk production.